Perencanaan Investasi Pembangunan Perumahan Di Desa Dibal Kecamatan Ngemplak Kabupaten Boyolali - Argamulya, Kurniawan, Ir. H. Muhammad Nur Sahid, M.M., M.T (2016)
Rapid development of residential in the Boyolali area, especially in Ngemplak Subdistrict, Dibal Village, Boyolali Regency. At this location the developing residential projects is very rapidly because of the strategic location very close to the Central Sub-district Ngemplak. To plan a residential investment projects, generally require a very large cost, thus he had to do the feasibility study in order to make this investment does not adversely. Spreading a detailed questionnaire is conducted that aims to find out how the needs of residential houses in the village of Dibal and doing feasibility study of economic aspects which consists of PP, ROI, NPV,IRR, BCR, IP, and BEP to know when the break-even point investment been gained. After conducted analysis, conclusion, 17 residential units is planned in the Dibal village with area 2945 m2, with economic analysis include PP by a typical flow of annual fixed amount obtained value 21 months 24 days, while the typical flow of the annual amount not fixed values obtained 20 months 16 days, ROI before tax is obtained 4,586% monthly = 55,03% a year, ROI after tax is obtained ] 4,13% monthly = 49,53% a year, NPV has positive value of Rp 642.440.364,92; IRR has value of 18,71% > interest rates 10%, BCR has value of 1,084 > 1, IP has value of 1,084 > 1, and BEP achieved in sales 12 house type which is detailed type house one by one, there are type 36/66 = 4 unit, type 45/102 = 4 unit, type 65/108 = 2 unit, and type 80/140 = 2 unit. Thus investment planning of residential development in the Dibal village, Ngemplak Subdistrict, Boyolali Regency is worthy.